Uncertainty analysis for material measurements using the vector network analyzer. Issue 8 (27th May 2016) - Shoaib, Nosherwan; Sellone, Marco; Brunetti, Luciano; Oberto, Luca
ABSTRACT: This article presents the characterization measurements and related uncertainty evaluation of a non‐magnetic material using the Vector Network Analyzer (VNA) at microwave frequencies. The permittivity of the material under test is computed from the scattering parameters (S‐parameters). The aim of the work is to highlight the different uncertainty contributions affecting the permittivity. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1841–1844, 2016